2003
DOI: 10.1017/s1074070800005915
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Stocking Density for Dual-Purpose Winter Wheat Production

Abstract: Dual-purpose winter wheat production is an important economic enterprise in the southern Great Plains of the United States. Because of the complex interactions involved in producing wheat grain and beef gain from a single crop, stocking density is an important decision. The objective of the research is to determine the stocking density that maximizes expected net returns from dual-purpose winter wheat production. Statistical tests rejected a conventional linear-response plateau function in favor of a linear-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…To determine if there is an economic difference between the two models, the expected profit maximizing stocking densities were determined and are presented in Table 3. For the LRSP model, the expected profit maximizing levels were determined as in Kaitibie et al (2003a). For the SR model, the necessary two‐dimensional integral was derived, and the optimum level was determined by grid search.…”
Section: Data and Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine if there is an economic difference between the two models, the expected profit maximizing stocking densities were determined and are presented in Table 3. For the LRSP model, the expected profit maximizing levels were determined as in Kaitibie et al (2003a). For the SR model, the necessary two‐dimensional integral was derived, and the optimum level was determined by grid search.…”
Section: Data and Applicationmentioning
confidence: 99%
“…Livestock grazing practices generally follow patterns that can be explained by the von Liebig hypothesis, characterized by nonsubstitution between inputs and a gain/yield plateau (Hart et al 1988; Kaitibie et al 2003a). The von Liebig hypothesis suggests that output is directly related to the amount of the most limiting production input.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question is then does stocker grazing earn enough added revenue to offset the reduction in wheat grain returns? Kaitibie et al (2003) reported wheat stocker weight gains of 0.99 kg d –1 and an optimal stocking density of 1.48 steers ha –1 , generating 1.47 kg d –1 ha –1 of weight gain. Stockers can be expected to graze for approximately 100 days, yielding a total stocker gain of 147 kg ha –1 .…”
Section: Economic Considerations For Seed Treatments With and Withoutmentioning
confidence: 99%